The algorithm knows I’m Black: from users to subjects - Meyerend, Daniel (Media, culture & society, 2023)
In October of 2018, several Black Netflix users took to Twitter to air their grievances about images in movie thumbnails featuring Black actors with minor roles, even when the movie itself was a majority white cast. In response to these critiques, Netflix claimed that because users are not asked about their racial identity, it is impossible to personalize the individual Netflix experience using identity markers. This article explores the interplay between algorithmic cultures and representations of race, examining the identity and voices of users and how their agency is affected within algorithmic systems. Users are seeking agentic traction in these algorithmic spaces, and this research begins to address how Black users are positioning themselves to make sense of the digital constraints placed on them. Black subscribers of Netflix heavily critiqued the algorithms used to advertise content to them, and I examine how Netflix constructs Black users as Black subjects in order to keep them engaged with the platform.